Giant tunability of upconversion photoluminescence in Er3+-doped (K, Na)NbO3 single crystals. Issue 36 (6th September 2019) - Xue, Saidong; Deng, Hao; Xie, Qingxiu; Hu, Yuqing; Yan, Jianmin; Zhao, Xiangyong; Wang, Feifei; Zhang, Quan; Luo, Laihui; Deng, Chenguang; He, Chongjun; Lin, Di; et al.
Abstract : Giant tunability of UC PL by oxygen vacancy control was realized in Er-KNN single crystals grown for the first time. Abstract : Perovskite oxides with luminescent ions hold great promise in optoelectronic devices because of their outstanding thermal stabilities and electro-optic performance. As one typical perovskite upconversion (UC) host material, lead-free potassium sodium niobate ((K, Na)NbO3 /(K x Na1− x )NbO3 or KNN) has attracted much attention in recent years. In the present work, a novel routine was developed to tune the upconversion photoluminescence (UC PL) performance by controlling the oxygen vacancy concentration in the KNN matrix, based on the 0.1% Er 3+ -doped KNN (Er-KNN) single crystals grown for the first time. UC PL properties, conductivity and defect chemistry of the single crystals were systematically investigated. The UC PL intensity of the as-grown Er-KNN material could be enhanced by 20 times after oxygen atmosphere annealing at 800 °C and fully quenched after vacuum annealing. What's more, by annealing under an oxygen atmosphere and vacuum, the conductivity of the Er-KNN sample was successfully tuned for more than 8 orders of magnitude. The super-wide range tunability of UC PL performance and conductivity could be explained by oxygen vacancies which gave rise to Nb 5+ –Nb 4+ valence alternation. Because of the modulated photoluminescence properties and conductivity, our grown Er-KNN single crystals have great potential for use in multifunctional devices.